Integrated Management of Childhood Illness implementation in Nepal: understanding strategies, context, and outcomes - Raj Kumar Subedi; Amelia VanderZanden; Kriti Adhikari; Sasmrita Bastola; Lisa R. Hirschhorn; Agnes Binagwaho; Mahesh Maskey (BMC, 2024)
Abstract Background Health system-delivered evidence-based interventions (EBIs) are important to reducing amenable under-5 mortality (U5M). Implementation research (IR) can reduce knowledge gaps and decrease lags between new knowledge and its implementation in real world settings. IR can also help understand contextual factors and strategies useful to adapting EBIs and their implementation to local settings. Nepal has been a leader in dropping U5M including through adopting EBIs such as integrated management of childhood illness (IMCI). We use IR to identify strategies used in Nepal's adaptation and implementation of IMCI. Methods We conducted a mixed methods case study using an implementation research framework developed to understand how Nepal outperformed its peers between 2000-2015 in implementing health system-delivered EBIs known to reduce amenable U5M. We combined review of existing literature and data supplemented by 21 key informant interviews with policymakers and implementers, to understand implementation strategies and contextual factors that affected implementation outcomes. We extracted relevant results from the case study and used explanatory mixed methods to understand how and why Nepal had successes and challenges in adapting and implementing one EBI, IMCI. Results Strategies chosen and adapted to meet Nepal's specific context included leveraging local research to inform national decision-makers, pilot testing, partner engagement, and building on and integrating with the existing community health system. These cross-cutting strategies benefited from facilitating factors included community health system and structure, culture of data use, and local research capacity. Geography was a critical barrier and while substantial drops in U5M were seen in both the highest and lowest wealth quintiles, with the wealth equity gap decreasing from 73 to 39 per 1,000 live births from 2001 to 2016, substantial geographic inequities remained. Conclusions Nepal's story shows that implementation strategies that are available across contexts were key to adopting and adapting IMCI and achieving outcomes including acceptability, effectiveness, and reach. The value of choosing strategies that leverage facilitating factors such as investments in community-based and facility-based approaches as well as addressing barriers such as geography are useful lessons for countries working to accelerate adaptation and implementation of strategies to implement EBIs to continue achieving child health targets.